2020
DOI: 10.3390/ijerph17041193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Contextual Variables on Physical and Technical Performance in Male Amateur Basketball: A Case Study

Abstract: Currently, most basketball research is focused on professional and elite players. Studies at the amateur level are important to explain the physical and technical demands of competition and thus improve players’ and teams’ performance. The purpose of the present study was to describe the competitive demands of an amateur-level basketball team and to analyze the influence of different situational variables on the physical and technical performance indicators. Eleven amateur senior basketball players participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The reason is that excessive trunk and pelvic motion in addition to the lack of lumbopelvic control during the swing phase of the running action is closely related to the injury risk [ 13 ]. Most studies usually analyze the number of horizontal trunk accelerations per intensity zones based on the activity-demands profile of the sport (e.g., soccer: 0–5 G, 5–6 G, >9 G; basketball: 0–3 G, 3–5 G, 5–8 G, >8 G; rugby: 0–6 G, 6–7 G, 7–8 G, 8–10 G, 10–12 G, >12 G; endurance trail running: 1G ranges from 0 to 30 G) [ 38 , 39 , 40 , 41 ]. However, these studies neither analyzed the total of trunk accelerations nor the average magnitude of these trunk accelerations (i.e., triaxial G-forces), which has been considered as a key external load indicator in professional soccer by a principal component analysis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that excessive trunk and pelvic motion in addition to the lack of lumbopelvic control during the swing phase of the running action is closely related to the injury risk [ 13 ]. Most studies usually analyze the number of horizontal trunk accelerations per intensity zones based on the activity-demands profile of the sport (e.g., soccer: 0–5 G, 5–6 G, >9 G; basketball: 0–3 G, 3–5 G, 5–8 G, >8 G; rugby: 0–6 G, 6–7 G, 7–8 G, 8–10 G, 10–12 G, >12 G; endurance trail running: 1G ranges from 0 to 30 G) [ 38 , 39 , 40 , 41 ]. However, these studies neither analyzed the total of trunk accelerations nor the average magnitude of these trunk accelerations (i.e., triaxial G-forces), which has been considered as a key external load indicator in professional soccer by a principal component analysis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of accelerometers is only important if the output range of each accelerometer is considered. WIMU PRO is composed of four accelerometers with specific output ranges ±16g, ±16g, ±32g and ± 400g [47,48,72] while Optimeye S5 is composed of three ±16g accelerometers [49]. This technical feature is very important due to the second device cannot detect the peak of force generated when a collision is over than 16g.…”
Section: Accelerometer Technical Featuresmentioning
confidence: 99%
“…Although multiple investigations have measured the PL and PL/min during official games and games-based drills in basketball (Schelling and Torres, 2016 ; Fox et al, 2018 ; Vázquez-Guerrero et al, 2018 , 2019a , b ; Pino-Ortega et al, 2019 ; Conte et al, 2020 ; Fernández-Leo et al, 2020 ; García et al, 2020 ; O'Grady et al, 2020 ; Portes et al, 2020 ; Ransdell et al, 2020 ), no study has assessed the external load imposed during single basketball-specific activities measured via TMA. To the best of our knowledge, a similar approach was previously used only in netball, with two official games analyzed via TMA and IMUs, revealing that on average the highest PL was registered during off-ball guarding actions (Bailey et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that playing position can affect players' physical demands during official games (Puente et al, 2017 ; Stojanović et al, 2018 ; Vázquez-Guerrero et al, 2018 , 2019b ; Pino-Ortega et al, 2019 ; Ferioli et al, 2020b ; Fernández-Leo et al, 2020 ; García et al, 2020 ). Specifically, while previous research has identified positional differences in the frequency and duration of high-intensity activities during basketball games (Stojanović et al, 2018 ), there is no indication of the external load registered during single high-intensity activities according to playing position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation